2009
DOI: 10.1038/sj.bjc.6605459
|View full text |Cite
|
Sign up to set email alerts
|

Short-term health-related quality of life consequences in a lung cancer CT screening trial (NELSON)

Abstract: BACKGROUND: In lung cancer CT screening, participants often have an indeterminate screening result at baseline requiring a follow-up CT. In subjects with either an indeterminate or a negative result after screening, we investigated whether health-related quality of life (HRQoL) changed over time and differed between groups in the short term. METHODS: A total of 733 participants in the NELSON trial received four questionnaires: T0, before randomisation; T1, 1 week before the baseline screening; T2, 1 day after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 22 publications
7
106
0
4
Order By: Relevance
“…83,84 The psychosocial impact of LDCT screening for lung cancer has been examined in controlled trials outside the UK, in terms of effects of both trial allocation and screening results. [85][86][87][88][89][90][91] Overall, evidence from these trials suggests that LDCT screening does not produce long-term anxiety or other adverse effects that could deter high-risk individuals from further help-seeking or future participation in a lung screening programme. However, it is important to examine psychosocial effects within the UKLS context to ensure that any future lung screening programme is tailored to the specific needs of the UK high-risk population.…”
Section: Introductionmentioning
confidence: 99%
“…83,84 The psychosocial impact of LDCT screening for lung cancer has been examined in controlled trials outside the UK, in terms of effects of both trial allocation and screening results. [85][86][87][88][89][90][91] Overall, evidence from these trials suggests that LDCT screening does not produce long-term anxiety or other adverse effects that could deter high-risk individuals from further help-seeking or future participation in a lung screening programme. However, it is important to examine psychosocial effects within the UKLS context to ensure that any future lung screening programme is tailored to the specific needs of the UK high-risk population.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Only a limited number of studies to date, however, have reported on the presence of psychological factors in a high-risk lung cancer screening population. [8,23] Of these, the main focus has been predominantly on stress related to awaiting results [23] and/or the anxiety associated with the presence of indeterminate findings. [3,8,9] Byrne et al evaluated the psychological impact of lung cancer screening in 400 patients using surveys collected before and after screening, at 6 and 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…[8,23] Of these, the main focus has been predominantly on stress related to awaiting results [23] and/or the anxiety associated with the presence of indeterminate findings. [3,8,9] Byrne et al evaluated the psychological impact of lung cancer screening in 400 patients using surveys collected before and after screening, at 6 and 12 months. The study data included demographic information, state/trait anxiety, fear of cancer and perceived risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample of Dutch and Belgian persons (50-75 years old) registered in population registries were inquired about their health and smoking behaviour [24]. Participants who had smoked ≥15 cigarettes per day for 25 years or ≥10 cigarettes for 30 years and were current smokers or had quit <10 years ago were included.…”
Section: Participantsmentioning
confidence: 99%